Robust tracking control design for Unicycle Mobile Robots with input saturation. (February 2021) - Martínez, Edgar A.; Ríos, Héctor; Mera, Manuel
Abstract: In this paper a robust tracking control strategy is proposed for Unicycle Mobile Robots (UMRs) under the influence of some disturbances. The proposed strategy is designed taking into account the perturbed kinematic model and it is based on two robust control techniques: Sliding-Mode Control (SMC) and Attractive Ellipsoid Method (AEM). The control of the heading angle is designed by means of a saturated SMC algorithm while the position control is designed by means of the AEM considering a Barrier Lyapunov function (BLF) approach. Simulation results illustrate the performance of the proposed robust controller compared to a classic UMR controller. Finally, some experimental results and comparisons illustrate the performance of the proposed strategy.